Efektivitas Model STAD Terhadap Hasil Belajar Matematika Ditinjau dari Self Efficacy Peserta Didik Kelas 5 SDN 1 Sidorahayu - Jaelani Jaelani; Meriyati Meriyati; Mukti Amini; Komarudin Komarudin (ARITHMETIC: Academic Journal of Math, 2019)
This study aims to determine the effectiveness of cooperative learning model on the STAD (Student Team Achievement Division) type reviewed from students’ self efficacy toward mathematics learning outcomes. In this study, the hypothesis test uses two way anava analysis with a significance level of α = 0.05. The population of this study was the fifth grade students of SDN 1 Sidorahayu which are divided into two study groups. Meanwhile, the sample of this study is students in the fifth grade who also divided into two study groups. Test results show that the test instruments are valid with a reliability index of r11> 0.70 and a difficulty index of p> 0.70 for easy criteria, and p